Prospects of Directly Reprogrammed Adult Human Neurons for Neurodegenerative Disease Modeling and Drug Discovery: iN vs. iPSCs Models - Zhang, Ying; Xie, Xinyang; Hu, Jiangnan; Afreen, Kazi Sabrina; Zhang, Chun-Li; Zhuge, Qichuan; Yang, Jianjing (Frontiers in Neuroscience, 2020)
A reliable disease model is critical to study specific disease mechanism as well as for discovery and development of new drugs. Despite providing crucial insights into mechanisms of neurodegenerative diseases, translation of this information to develop therapeutics in clinical trials have been unsuccessful. Reprogramming technology to convert adult somatic cells to induced Pluripotent Stem Cells (iPSCs) or directly reprogramming adult somatic cells to induced Neurons (iN), has allowed for creation of better models to understand the molecular mechanisms and design of new drugs. In recent times, the iPSC technology has been commonly used for modeling of neurodegenerative diseases and drug discovery. However, several technological challenges have limited application of iN. As evidences suggest, iN for modeling of neurodegenerative disorders is advantageous compared to those derived from iPSCs. In this review, we will compare iPSCs and iN models for neurodegenerative diseases and their potential applications in future.